Providing Equitable and Accessible Mental Health Care to Minoritized Children and Families in Canada: A Case Example - Zepeda, Michelle S.; Racine, Nicole (Canadian Journal of Counselling and Psychotherapy, 2025)
Minoritized children and their families living in Canada face a number of barriers to accessing mental health care. This article explores some common barriers related to location, race and ethnicity, language, and financial considerations that minoritized children and their families face when they seek or receive psychosocial interventions within a Canadian context. Practical accommodations and strategies used to address these barriers are discussed and illustrated by an example of work with a Latin American youth and her parents. Implications for the psychosocial treatment of minoritized children and their families are outlined, and calls to action for individual counsellors and for the field of counselling psychology to address barriers are discussed.